The Impact of organizational improvisation on Entrepreneurial Performance: An Analytical Research at the Ministry of Education in Iraq - Yaseen Ekrayyem Hammadi ALFalloji; Salah Abd Al-Qadeer Ahmed Al Nuiami (Eximia, 2024)
The current research aims to study the effect of organizational improvisation on the entrepreneurial performance of a sample of employees in the Iraqi Ministry of Education. A purposive random sample of 175 individuals was selected based on a data collection questionnaire. Organizational improvisation includes five dimensions (intuition, innovation, adaptation, opportunity, and risk perception). Entrepreneurial performance addresses four dimensions (proactive planning, entrepreneurial indicator, innovation and creativity, efficiency and effectiveness). The research highlights organizational improvisation in educational administrations to ensure the success of entrepreneurial performance in Iraqi educational institutions. The research problem revolves around the extent of the impact of organizational improvisation in enhancing entrepreneurial performance practices in the Iraqi Ministry of Education. The results indicate the need for the Iraqi Ministry of Education to adopt a strategic direction through organizational improvisation of its directorates, which leads to developing the educational landscape and understanding the importance of appropriate direction to achieve institutional leadership performance.